Worship, Technology and Identity: A Deaf Protestant Congregation in Urban China. (August 2019) - McLeister, Mark
Abstract : This paper 1 analyses a Deaf community in urban China and explores the extent to which this particular community has contextualised a Protestant message centred on understandings of sin as a disability. The construction of this message is based on a shared identity as both Deaf and Protestant and is mediated through a shared practice of signing and a common written language (Chinese). Circulation of this message is facilitated by technology and social media. Based on ethnographic data generated in a Deaf congregation in Yantai, Shandong province, I argue that while the message of this particular group is highly contextualised, the community has both national and transnational ties, linking it to a range of Protestant groups both within and outside mainland China. This paper furthers our understanding of how Christian identity is shaped in contemporary China.